Mediterranean-DASH Diet Intervention for Neurodegenerative Delay Diet and Psychological Problems in Maintenance Hemodialysis Patients by the Structural Equation Modeling Analysis of Malnutrition and Inflammation Markers Approach - Acik, Murat; Gu, Aylin Bayindir; Ekici, Ayse; Yilmaz, Feray Cagiran; Kucuju, Mehmet (W B Saunders Co-Elsevier Inc, 2025)
Objective: Although it is known that diet quality affects psychological problems in hemodialysis (HD) patients, there is need to explain the role of modifiable risk factors in this relationship. Therefore, the aim of this study was (1) to investigate the relationship between diet quality and modifiable risk factors to depression and anxiety in end-stage renal disease patients receiving maintenance HD; (2) to explore the mediating roles of modifiable factors in the relationship with diet quality to depression and anxiety. Methods: This cross-sectional study included 216 patients with end-stage renal disease receiving maintenance HD treatment. We assessed participants' dietary records for Mediterranean-DASH Diet Intervention for Neurodegenerative Delay (MIND) quality, Global Leadership Initiative on Malnutrition criteria for malnutrition and Hospital Anxiety and Depression Scale for psychological problems. Furthermore, biochemical findings and anthropometric measurements were performed to evaluate nutritional markers, metabolic risk factors and inflammation. We applied hierarchical regression analysis to estimate modifiable risk factors for depression and anxiety and structural-equation-modeling analysis to determine the mediating role of modifiable risk factors between diet quality and psychological problems. Results: Depression symptoms were observed in 59.2% (n = 128) of the participants, whilst the rate was 35.1% (n = 76) for anxiety. Depression and anxiety were found to be negatively correlated with MIND levels after covariate adjusting model, and the rates of explanation were found to be 16.2% and 12.2%, respectively. C-reactive protein (CRP), albumin levels and the presence of malnutrition were shown to be significant predictors of depression (dF = 14.761 and dR2: 0.071 for covariate-adjusted model). Albumin levels, CRP, HD duration, and malnutrition were found to be independent predictors of anxiety (dF = 16.174 and dR2: 0.077 for covariate-adjusted model). It was found that CRP and malnutrition partially mediated the association of MIND score with depression, and CRP mediated the association with anxiety. Conclusion: It was concluded that adherence to the MIND diet is associated with a better nutritional profile and reduced inflammation, which in turn may be linked to fewer psychological problems.These further studies are needed to validate and expand upon our findings.
Keywords: diet quality; depression; anxiety; inflammation; nutritional markers